Analysis of the Causes of Lumbar Disc Herniation in Patients Treated Neurosurgical Due to it - Joanna Rosińczuk; Kamila Owsikowska; Aleksandra Kołtuniuk (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. Discopathy is a serious social problem because it affects professionally active people and often at a very young age (usually discopathy occurs in 3rd–4th decade of life). The etiology and pathogenesis of lumbar disc disease is not known in detail. Studies say about many factors predisposing to disease of the intervertebral disc. Understanding the causes of discopathy can contribute to better prevention of this disease. Aim. Study the causes of lumbar disc herniation and to evaluate the respondents’ knowledge about them. Material and Methods. The study was conducted among 67 patients with lumbar discopathy hospitalized in the Department of Neurosurgery or treated in the neurosurgical practice of Lower Silesia Specialized Hospital name Tadeusz Marciniak in Wroclaw. The study was performed with the use of diagnostic questionnaire using the survey technique. The obtained data were processed with statistical analysis software Statistica 10 underwent statistical analysis. Results. Analysis of the research material has shown that: over 55% respondents think that the cause of lumbar disc herniation is their work; over 40% of respondents in the course of work lift weights exceeding acceptable standards; the vast majority of respondents feel pain of the spine (located on the VAS (Visual Analogue Scale) in the range of 7 to 10; almost half of respondents are overweight (25 <BMI> 30). Conclusions. 1) Patients with lumbar disc herniation suffer from severe back pain. 2) Patients suffering from disc herniation often at work take forced sitting position or in the wrong way lift weights. 3) Patients with disc herniation do not have knowledge about the prevention of this disease. (JNNN 2015;4(4):152–157)